Strategi Pengembangan Bisnis Yang Berbasis Lingkungan Pada Usaha Mikro Di Kota Semarang - Eny Trimeiningrum; Meniek Srining Prapti; Bernadeta Irmawati (JEMAP, 2023)
The research intends to find/compile alternative strategies for the development of ecopreneur businesses in micro-enterprises in the city of Semarang. Focus Group Discussion (FGD) was conducted with respondents who became the research sample in order to identify the strengths, weaknesses, threats, and business opportunities of ecopreneurs in general. From the results of the SWOT analysis, several alternative strategies are proposed for business development, including: relearning by attending workshops or training related to coloring and the production process of friendly products by reusing handicraft exhibition events or exhibitions held after the Covid-19 pandemic; maximize the use of social media as a means of promotion and marketing; provide education to the public about environmentally friendly products to consumers through brochures, labeling, or packaging; further enhance collaboration among craftsmen of environmentally friendly products so that product quality becomes better; as well as learning how to produce by foreign producers so that they are more capable of producing in larger quantities. Meanwhile, input for relevant government agencies in Semarang is to be able to collaborate with micro-scale ecopreneurs in Semarang  better in order to provide education to increase public awareness about environmentally friendly products.